Ex-Vivo Normothermic Limb Perfusion With a Hemoglobin-Based Oxygen Carrier Perfusate. (19th February 2020) - Said, Sayf A; Ordeñana, Carlos X; Rezaei, Majid; Figueroa, Brian A; Dasarathy, Srinivasan; Brunengraber, Henri; Rampazzo, Antonio; Gharb, Bahar Bassiri
Abstract: Introduction: Ex-vivo normothermic limb perfusion (EVNLP) has been proven to preserve limb viability better than standard cold storage. Perfusates containing packed red blood cells (pRBC) improve outcomes when compared to acellular perfusates. Limitations of pRBC-based perfusion include limited availability, need for cross match, mechanical hemolysis, and activation of pro-inflammatory proteins. Hemoglobin-based oxygen carrier (HBOC)-201 (Hemopure) is a solution of polymerized bovine hemoglobin, characterized by low immunogenicity, no risk of hemolytic reaction, and enhanced convective and diffusive oxygen delivery. This is a preliminary study on the feasibility of EVNLP using HBOC-201 as an oxygen carrier. Materials and Methods: Three porcine forelimb perfusions were performed using an established EVNLP model and an HBOC-201-based perfusate. The perfusion circuit included a roller pump, oxygenator, heat exchanger, and reservoir. Electrolytes, limb temperature, weight, compartment pressure, nerve conduction, and perfusion indicated by indocyanine green angiography and infra-red thermography were monitored. Histological evaluation was performed with hematoxylin and eosin and electron microscopy. Results: Three limbs were perfused for 21.3 ± 2.1 hours. Muscle contractility was preserved for 10.6 ± 2.4 hours. Better preservation of the mitochondrial ultrastructure was evident at 12 hours in contrast to crystallization and destruction features in the cold-storage controls. Conclusions: An HBOC-201-EVNLP produced outcomes similar to RBC-EVNLP with preservation of muscle contractility and mitochondrial structure.